Given the following fraction: $$\frac{1-\exp\left(-\frac{1}{1+tx}\right)}{1-\exp\left(\frac{1}{1+t}\right)}$$

I need to find the limit as $t$ tends to infinity, so:

$$\lim_{t\rightarrow\infty} \frac{1-\exp\left(-\frac{1}{1+tx}\right)}{1-\exp\left(\frac{1}{1+t}\right)}$$

A formal proof is not needed.

  • $\begingroup$ For $u$ close to $0$, $\exp(-u)$ is approximately $1-u$. $\endgroup$ – John Dawkins Jan 2 '16 at 15:57

We see that for $t\to \infty$ the arguments of the exponential functions tend to zero. Therefore, since

$$1+x\le e^x\le \frac{1}{1-x}=1+x+O(x^2)$$

for $x<1$, we can simply write heuristically

$$e^{x}\approx 1+x$$

Then, we have for $x\ne 0$

$$\frac{1-e^{-1/(1+tx)}}{1-e^{1/(1+t)}}\approx -\frac{1+t}{1+tx}\to -\frac1x$$

And for $x=0$ we have

$$\frac{1-e^{-1}}{1-e^{1/(1+t)}}\to -\infty$$

  • $\begingroup$ Happy New Year !! my friend. $\endgroup$ – Claude Leibovici Jan 2 '16 at 16:59
  • $\begingroup$ @ClaudeLeibovici Happy New Year to you also!! I hope you are doing well. $\endgroup$ – Mark Viola Jan 2 '16 at 17:02

The function $f(x) = 1 - \exp(x)$ can be approximated, around $x = 0$, by the function $-x$. You can graph them to check this or just use the McLaurin expansion of $\exp x$.

The limit is then: $$\lim_{t \to +\infty} -\frac{1 + t}{1 + tx} = \lim_{x \to +\infty} -\frac{1 + \frac 1t}{x + \frac 1t} = -\frac1x.$$


When $t$ grows, the terms $1$ in the exponentials become neglectible and one can trade the limit at infinity for one at zero:


Then by L'Hospital,



Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.